Isotopic analysis of snow from Dome C indicates changes in the source of atmospheric lead over the last fifty years in East Antarctica. (September 2020) - Bertinetti, Stefano; Ardini, Francisco; Vecchio, Maria Alessia; Caiazzo, Laura; Grotti, Marco
Abstract: Lead (Pb) concentration and Pb isotope ratios have been determined in 109 snow pit samples collected at Dome C, on the East Antarctic Plateau, corresponding to the period 1971–2017. The Pb concentration was 8.2 ± 1.0 pg g −1 (mean ± 95%-confidence interval), with a decreasing trend from the early 1990s (the median Pb concentration halved from 9.0 pg g −1 in 1970–1980 to 4.4 pg g −1 in 2010–2017). The 206 Pb/ 207 Pb and 208 Pb/ 207 Pb ratios were 2.419 ± 0.003 and 1.158 ± 0.003 (mean and 95%-confidence interval), respectively. The temporal variations of Pb isotopic composition from 1970 to mid-1990s reflect the changes in the consumption of Pb-enriched gasoline in the Southern Hemisphere, whereas the subsequent increase of the Pb isotope ratios is ascribed to a shift toward the natural isotopic signature. Accordingly, the anthropogenic Pb contribution decreased from (61 ± 3)% in 1980–1990 to (49 ± 10)% in 2010–2017. The measured ratios suggest that Australia has been a significant source of anthropogenic Pb to Antarctica, even in recent times. Differences and similarities among Pb content and isotopic composition in various sites across Antarctica have been displayed by principal component analysis, indicating that the altitude and the distance from the coast significantly affect the Pb content, while the Pb isotopic signatures are not influenced by these parameters. Graphical abstract: Image 1 Highlights: The median Pb concentration halved from 9.0 pg g −1 in 1970-80 to 4.4 pg g −1 in 2010-17. The contribution of anthropogenic Pb was 61 ± 3% in 1980-90 and 49 ± 10% in 2010-17. Australia has been a significant source of anthropogenic Pb to Antarctica. Altitude and distance from the coast significantly affect the Pb content but not its isotopic signature.